(untitled) (Rainbow Journal, 2019)
The problems of mathematics teachers to using ICT in mathematics teaching represent the infrastructure and resources, skills and training, and policy-related problems. The aim of the study was to find the effect of the problems of using ICT on the purposes of its usage in mathematics teaching among mathematics teachers of secondary level. 342 mathematics teachers from secondary schools of Kathmandu, Kailali, and Kanchanpur were selected purposively and data was analyzed by Structural Equation Modeling (SEM). The finding indicates that the mathematics teachers of Nepal were facing several problems related to infrastructure and resources, skills and training, and policy. The problems of using ICT in mathematics teaching have no effect on the purpose of using ICT in mathematics teaching however the purposes of using ICT in teaching and learning and documentation and internet surfing had significant contribution to determine alternative dimensions.